PENGARUH KEPEMILIKAN INSTITUSI, SIZE DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK DENGAN LEVERAGE SEBAGAI PEMEDIASI (Studi pada Perusahaan Food and Beverage Periode 2013-2017) - Lulukil Maknun, 14.05.52.0241; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2019)
This study examines the effect of institutional ownership, company size, and profitability on tax avoidance with leverage as a mediator. The sample in this study used 60 data from Food and Beverage companies listed on the Indonesia Stock Exchange for the period 2013-2017 using the purposive sampling method. The analytical tool used is multiple linear regression test, model test, and hypothesis testing. Based on the research that has been done, the results of this study indicate that institutional ownership has ano significant negatif effect on leverage, the size of the company has a significant positive effect on leverage, profitability has a no significant positive effect on leverage, institutional ownership has a no significant positive effect on tax avoidance, the size of the company has a no significant positive effect on tax avoidance, profitability has a no significant positive effect on tax avoidance, leverage has a no significant positive effect on tax avoidance.